2011
DOI: 10.4103/0974-1208.92290
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent genuine empty follicle syndrome

Abstract: Failure to aspirate oocytes after ovarian stimulation for an in vitro fertilization cycle, after confirming normal folliculogenesis and steroidogenesis occurs in about 0.2–7% of the cycles. This condition is known as empty follicle syndrome. Most of the time, it may be due to human or pharmacological error, but rarely there is an entity called genuine empty follicle syndrome where no known cause can be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…[16,17] Yanlış hCG uygulaması ve hCG farmakolojik özel-liklerinde bozulma şeklinde açıklanabilir etiyolojisi olduğu gibi hiçbir sebebin bulunamadığı durumlar da olmaktadır. [18] Gonadotropin salgılatıcı hormon (GnRH) antagonisti sikluslarında endojen LH salınımı için GnRH agonisti kullanıldığında boş folikül sendromuyla karşı-laşma oranı %1.4 oranında bildirilmektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[16,17] Yanlış hCG uygulaması ve hCG farmakolojik özel-liklerinde bozulma şeklinde açıklanabilir etiyolojisi olduğu gibi hiçbir sebebin bulunamadığı durumlar da olmaktadır. [18] Gonadotropin salgılatıcı hormon (GnRH) antagonisti sikluslarında endojen LH salınımı için GnRH agonisti kullanıldığında boş folikül sendromuyla karşı-laşma oranı %1.4 oranında bildirilmektedir.…”
Section: Discussionunclassified
“…Stimülasyona hastanın over kapasitesine göre rekombinant FSH, human menapozal gonadotropin veya letrozol ile menstrüel siklusun ikinci ya da üçüncü günü başlandı. En az üç tane 17 …”
Section: Hastalar Ve Yöntemunclassified
“…Zreik et al [4] suggested that the rate of recurrence of EFS increased with patients' age (24 % in those 35-39 years of age; 57 % in those over 40 years of age), and that ovarian aging might be implicated in the etiology of EFS and its recurrence. Smisha et al [17] mentioned that EFS did not represent a permanent pathophysiological condition because of its sporadic occurrence, and that it should be investigated whether there is some intrinsic ovarian pathology causing defective follicular development or a possible genetic cause to elucidate the occurrence of GEFS. There were 9 non-EF cycles among our 4 patients with EFS.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a systematic review and meta-analysis of five trials and 428 patients evaluated if follicular flushing can improve the outcomes of ART. 30 Adding FSH at the time of hCG trigger increases the likelihood of egg recovery. 28 However, another systematic review and meta-analysis of six randomized trials and 518 patients found that follicular flushing did not improve ART rates in normal responding patients or in poor responders.…”
Section: Follicular Flushingmentioning
confidence: 99%